Influence of ABCC2 and ABCC4 polymorphisms on tenofovir plasma concentrations in Thai HIV-infected patients - Kanokrat Rungtivasuwan (2018)
Copyright © 2015, American Society for Microbiology. All Rights Reserved. Tenofovir (TFV) is eliminated by renal excretion, which is mediated through multidrug-resistant protein 2 (MRP2) and MRP4, encoded by ABCC2 and ABCC4, respectively. Genetic polymorphisms of these transporters may affect the plasma concentrations of tenofovir. Therefore, the aim of this study was to investigate the influence of genetic and nongenetic factors on tenofovir plasma concentrations. A cross-sectional study was performed in Thai HIV-infected patients aged ≥18 years who had been receiving tenofovir disoproxil fumarate at 300 mg once daily for at least 6 months. A middose tenofovir plasma concentration was obtained. Multivariate analysis was performed to investigate whether there was an association between tenofovir plasma concentrations and demographic data, including age, sex, body weight, estimated glomerular filtration rate (eGFR), hepatitis B virus coinfection, hepatitis C v irus coinfection, duration of tenofovir treatment, concomitant use of ritonavir-boosted protease inhibitors, and polymorphisms of ABCC2 and ABCC4. A total of 150 Thai HIV-infected patients were included. The mean age of the patients was 43.9 ± 7.2 years. The mean tenofovir plasma concentration was 100.3 ± 52.7 ng/ml. In multivariate analysis, a low body weight, a low eGFR, the concomitant use of ritonavir-boosted protease inhibitors, and the ABCC4 4131T → G variation (genotype TG or GG) were independently associated with higher tenofovir plasma concentrations. After adjusting for weight, eGFR, and the concomitant use of ritonavir-boosted protease inhibitors, a 30% increase in the mean tenofovir plasma concentration was observed in patients having the ABCC4 4131 TG or GG genotype. Both genetic and nongenetic factors affect tenofovir plasma concentrations. These factors should be considered when adjusting tenofovir dosage regimens to ensure the efficacy and safety of a drug. (This study has been registered at ClinicalTrials.gov under registration no. NCT01138241.).